Kebertahanan Budaya Tembang Macapat dalam Tradisi Masyarakat Madura (Mengungkap Nilai-Nilai Pendidikan Islam) - Dewi Chairun Nisa; Siswanto Siswanto (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research focused on the reason Madurese community holding on the culture tembang macapat, islamic education values on tembang macapat culture and reading method tembang macapat to reveal Islam education values. This research used descriptive qualitative method in ethnography type, which means study research based on the whole culture. The result of this research is Madurese community still holding on macapat culture so it wouldn't extinct eroded by the times and the effort was do even macapat, arrange tranings the main things is concerning to macapat tembang, especially the teachers to developed onto educator. There are islam education values in macapat tembang such as faith value, in tembang artatĕ 'layang Pendowo: tasawuf, worship value, in tembang artatẻ ‘layang candrajagat, and morals value, in tembang artatẻ ‘layang. To read tembang macapat is in one stanza taken 4-4 syllables with play cengkok